AMMI ANALYSIS FOR STABILITY, ADAPTABILITY AND GE INTERACTION STUDIES IN COTTON (GOS SYPIUM HIRSUTUM L.) - M. Riaz; M. Naveed; J. Farooq; A. Farooq; A. Mahmood; Ch. M. Rafiq; M. Nadeem; A. Sadiq (Journal of Animal and Plant Sciences, 2013)
The present study was conducted to determine the yield stability, adaptability and to analyze the GE interaction of 9 cotton genotypes using a randomized complete block design (RCBD) with three replications at six locations in Punjab, Pakistan during the growing season of 2010 and 2011 (twelve environments). Additive main effects and multiplicative interactions (AMMI) analysis revealed that the major contributions to treatment sum of squares were environments (38.51%), GE (35.27%) and genotypes (26.22%), respectively, suggesting that the seed cotton yield of genotypes were under the major environmental effects of GE interactions. The first two principal component axes (PCA 1 and 2) cumulatively contributed to 64.34% of the total GE interaction and were significant (p ≤ 0.01). The biplot technique was used to identify appropriate genotype to special locations / environments. Results showed that genotypes BH-172, MNH- 814 and NIAB-2009 with the lowest interaction, and genotypes FH-4243, FH-113, CIM-496, CIM-573, VH-289 and MNH-886 with the highest interaction were the most stable and unstable genotypes, respectively. Moreover, genotypes NIAB-2009, MNH-814, VH-289, MNH-886, CIM-573 and BH-172 were more suitable for Sahiwal, Vehari and Bahawalpur conditions while genotypes FH-4243, FH-113 and CIM-496 were better suited for Faisalabad conditions.
Keywords: AMMI; biplot; stability analysis; GE interaction; seed cotton yield